The Scientists visits to Baghdad in the Period 447-647HD / 1055-1245AD Through the book The Supplement of History of Baghdad By Ibn Al Najjar: (Study The Causes) - Karam, Fatima; Okleh, Issam (Al-Adab Journal, 2023)
Life flourished in Baghdad in the period between the second half of the fourth century AH and the end of the first half of the sixth century AH. This is through advancement and development in the fields of literature, science and different kinds of arts. Thus, Baghdad became the sanctuary towards which every student of knowledge turned, and it became the pioneer of the Arab Islamic civilization in that period. Ibn al-Najjar explained this status in many texts through his book: The Tail of the History of Baghdad. He mentioned the sheikhs, modern scholars, and scholars who studied science in its schools, mosques, and institutes. He also mentioned the students who went to Baghdad in order to seek knowledge, and those who stayed for a long time to become sheikhs after that to transfer what they learned to their students. Ibn al-Najjar was able to paint a wonderful picture of Baghdad as a pioneer of science and scholars, and even showed the features of the picture in its finest details through authored texts.This study aims to reveal the scholars who visited Baghdad and settled there for a period of time or permanently, and the reasons that prompted them to such a visit. What is the extent of their influence on the scientific life in Baghdad or their influence on it? The study attempts to identify the geographical areas from which they came, their scientific specialization, their knowledge, and the sciences they took from Baghdad scholars and spread afterwards in their countries. The study concluded that 130 scholars visited Baghdad, and that they came to it from many parts of the Islamic world at the time, and that the reasons for the visit were multiple, but the most prominent of them was to seek knowledge.